Existence results for random impulsive neutral differential inclusions with lower semicontinuous. (1st January 2014) - Vinodkumar, A.
This article presents the results on existence of mild solutions for random impulsive neutral functional differential inclusions under sufficient conditions. The results are obtained by using the Krasnoselskii-Schaefer type fixed point theorem combined with the selection theorem of Berssan and Colombo for lower semicontinuous (LSC) maps with decomposable values.